Tropospheric ozone in the vicinity of the ozone hole - 1987 Airborne Antarctic Ozone Experiment - Gregory, Gerald L.; Warren, Linda S.; Hypes, Warren D.; Tuck, Adrian F.; Kelly, Kenneth K.; Krueger, Arlin J. (1989)
Results are presented on ozone measurements in the upper troposphere/lower stratosphere over Antarctica, obtained by NASA DC-8 aircraft during the August/September 1987 Airborne Antarctic Ozone Experiment. The ozone mixing ratios as high as several hundred ppbv were measured, but in all cases these ratios were observed in pockets of upper atmospheric air, both in the vicinity of and away from the location of the ozone hole. The background ozone values in the surrounding troposphere were typically in the range of 20-50 ppbv. Correlation of tropospheric ozone observations with the boundaries of the ozone hole differed in the course of the experiment. During the August 28 - September 2 flights, encounters with ozone-rich air were limited, and the background tropospheric ozone appeared to decrease beneath the hole. For the later flights, and as the ozone hole deepened, the ozone-rich air was frequently observed in the vicinity of the hole, and the average ozone values at the flight altitude were frequently higher than the background values.